Explaining the causal relationship between meta-parenting and parenting stress with the mediating role of mindfulness and parental self-efficacy in mothers of children with autism - Amirlou, Farahnaz; Saberi, Hayedeh; Hakim Shoushtari, Mitra (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The combination of mindfulness, parental self-efficacy and extra-parenting has a significant role in reducing parental stress, especially mothers, and parental stress management is important to promote well-being. Methods: The aim of this study was to investigate the mediating role of parental mindfulness and self-efficacy in explaining the causal relationship between extravagance and parental stress in mothers of children with autism. Correlational research design based on structural equation modeling and statistical population including all mothers with children 2 to 14 years old with autism referred to medical clinics in Tehran in 1400 that 250 people were selected by purposive sampling and Abidin parenting stress questionnaires. (1995) answered the Mindfulness Questionnaire (Brown and Ryan, 2003), the Trans parenting Questionnaire (Hawke and Holden, 2006) and the Parental Self-Efficacy Questionnaire (Dumka et al., 1996). Data analysis was performed using AMOS software version 24. Results: The results showed that the total path coefficient between extravagance and parental stress (p<0.01, β=-0.456) was negative and the path coefficient between mindfulness and parental stress (p <0.01, β=-0.474).) and parental self-efficacy and parental stress (p<0.01, β= -0.386) were negative and at the level of 0.01 were significant that parental self-efficacy and mindfulness were negatively related to the relationship between extra-parenting and parenting stress and mediated meaningfully. Conclusion: Trans parenting directly and parental mindfulness and self-efficacy directly and indirectly predict parental stress in mothers of children with autism. In order to provide interventions to reduce or prevent high levels of parental stress in families, it is necessary to pay special attention to interventions based on mindfulness, self-efficacy and extravagance in parent-child relationships.